Early epigenetic reprogramming in fertilized, cloned, and parthenogenetic embryos - Sepulveda-Rincon, Lessly P.; Solanas, Edgar del Llano; Serrano-Revuelta, Elisa; Ruddick, Lydia; Maalouf, Walid E.; Beaujean, Nathalie (Elsevier, 2016)
Despite ongoing research in a number of species, the efficiency of embryo production by nuclear transfer remains low. Incomplete epigenetic reprogramming of the nucleus introduced in the recipient oocyte is one factor proposed to limit the success of this technique. Nonetheless, knowledge of reprogramming factors has increased—thanks to comparative studies on reprogramming of the paternal genome brought by sperm on fertilization—and will be reviewed here. Another valuable model of reprogramming is the one obtained in the absence of sperm fertilization through artificial activation—the parthenote—and will also be introduced. Altogether the objective of this review is to have a better understanding on the mechanisms responsible for the resistance to reprogramming, not only because it could improve embryonic development but also as it could benefit therapeutic reprogramming research.